Implementation of hudud (or limits ordained by Allah for serious crimes) in Malaysia - Ali Mohamed, Ashgar Ali (Centre for Promoting Ideas (CPI), USA., 2012)
The arguments in relation to the implementation of hudud laws in Malaysia has once again resurfaced and is heatedly argued by the proponents of this laws and those who oppose its implementation. Some have contended that the implementation of hudud will only boost, and not deter crimes because of the high standard of proof imposed by syariah. Some went to the extent of saying that the implementation of hudud would only bring greater human rights disaster in Malaysia as the punishment is very cruel, inhuman or degrading. They argued that if the Malaysians are exposed to hudud punishment, Malaysians will gradually become inhumane. It was further contended that the nature of Hudud punishment is outdated and therefore, does not fit right into our system of society today. This article therefore, explores the above contention where the writer argued that Hudud is a mercy to mankind and not as some have claimed it to be barbarious, cruel and degrading. When it prevents crime, the society is safe and the punishment would be executed only when the necessary conditions of this crime is established beyond reasonable doubt. One execution however, is enough to bring a screeching halt to such crime or would significantly reduce the commission of the offence to a high degree.